SISTEM INFORMASI PERAMALAN PENJUALAN BARANG DI CV. ZAMI PUTRA MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - Nur Afifi, Yunis Fiatin; Rahmad, Cahya; Rosiani, Ulla Delfana (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Forecasting is important for companies in formulating corporate strategy in the future. Therefore, an appropriate forecasting method is absolutely necessary that the company can make a good business plan. CV. Zami Putra is a company convection. Every day serves many transactions for sell such as school uniforms, uniforms of various agencies, shirts, tracksuits that demand has a trend as well a seasonal factor. According to the number of transactions every month, the company needs a sales forecasting.This method is appropriate when the systematic component of demand has a level,a trend, and a seasonal factor also parameter α,β,and γ to increase the accuracy of forecasting Keyword :Triple Exponential Smoothing, Forecasting